Increasing Care for Patients with Mental Disorders Thought Community Empowerment: A Literature Review - Yosua Aldrin Kaligis; Shanti Wardaningsih (Universitas Aisyah Pringsewu, 2023)
Families and people with mental illnesses require community empowerment. When the environment is not empowered, it will have the impact of decreasing productivity levels. To realize mental health and public concern for people with mental disorders, it is necessary to make strategic efforts by developing mental health promotion programs as a preventive effort and increasing community empowerment to support mental health. aims to determine community empowerment in increasing care for patients with mental disorders. The following bibliographical databases were searched to identify potentially relevant documents: Google Scholar, Pubmed, and Proquest publications, 2017–2022. Findings from studies were extracted and aggregated, guided by the Joanna Briggs Institute (JBI). Literature review uses the PubMed, ProQuest, and Google Scholar databases. Keywords: